Air Traffic Management and Systems III Selected Papers of the 5th ENRI International Workshop on ATM/CNS (EIWAC2017) - Electronic Navigation Research Institute (Lecture Notes in Electrical Engineering, 2019)
This proceedings provides novel concepts and techniques for air traffic management (ATM) and communications, navigation, and surveillance (CNS) systems. The volume consists of selected papers from the 5th ENRI International Workshop on ATM/CNS (EIWAC2017) held in Tokyo in November 2017, the theme of which was "Drafting Future Skies". Included are key topics to realize safer and more efficient skies in the future, linked to the integrated conference theme consisting of long-term visions based on presentations from various fields. The proceedings is dedicated not only to researchers, academicians, and university students, but also to engineers in the industry, air navigation service providers (ANSPs), and regulators of aviation.